Toxic Effects of Excess Vitamins A, B6, and Folic Acid on the Nervous System - Yu Sun; Xiaofeng Yu; Yiliang Teng; Yanping Sun (Behavioural Neurology)
As one of the seven primary nutrients in the human body, vitamins are vital to maintaining good health. In recent years, there has been a completely new understanding of vitamins, and researchers have conducted more thorough investigations on them. These compounds, once viewed simply as supplemental nutrients, are now believed to play a more complex and critical role in human health. On the other hand, ingesting too much vitamins may cause negative health effects. Multiple studies have demonstrated a strong correlation between neurological problems and excessive vitamin intake. The purpose of this paper is to review the toxic effects of excessive vitamin intake on the nervous system, focusing on vitamin A and some of the B vitamins. It also analyzes the relationship between excessive vitamin intake and neurological dysfunction by reviewing the research findings in recent years, mainly including their possible mechanisms of action, clinical manifestations, and preventive measures, to provide ideas and inspiration for the subsequent clinical research.